La0.67Ce0.03Sr0.3MnO3-coupled microwave assisted ultra-fast synthesis of nanocrystalline cobalt oxide and Bismuth oxide - Rajagopal, Rajashree; Mona, J.; Joshi, Rakesh S.; Kale, Sangeeta N.; Pradhan, Sivararn; Gaikwad, A. B.; Ravi, V. (Materials Letters, 2008)
Bismuth hydroxide and Cobalt hydroxide gels were freshly prepared by adding aqueous sodium hydroxide to their corresponding nitrates under basic conditions. Then they were oven dried at 373 K and found to be amorphous in X-ray diffraction (XRD) study. They crystallized into their respective oxides by microwave irradiation (2.45 GHz) in merely 2 min using La0.67Ce0.03Sr0.3MnO3 (LCSMO) as couplant in a microwave domestic oven (similar to 100 W). This is the lowest temperature treatment and synthesis time so far reported in the literature for the formation of these systems. Formation of nanocrystallites of Bi2O3 (10 nm) and Co3O4 (15 nm) has been confirmed by XRD. Normally these hydroxides produce oxides only on heating at temperature >673 K or digesting them at 373 K for 4 - 6 hours as reported by us earlier. Microwave assisted heating proves to be a novel technology whose applications can be carefully harnessed due to its unique effects compared to the conventional heating, such as rapid volumetric heating, shortened reaction time and energy saving. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; Manganites; Microwave; Oxides